Adult neurogenesis in the ventral hippocampus decreased among animal models of neurodevelopmental disorders - Sun, Lihao; Ohashi, Nobuhiko; Mori, Takuma; Mizuno, Yuka; Zang, Weichen; Guo, Qi; Kouyama-Suzuki, Emi; Shirai, Yoshinori; Tabuchi, Katsuhiko (Frontiers in Neural Circuits, 2024)
IntroductionAutism spectrum disorder (ASD) is a neurodevelopmental condition characterized by deficits in social interaction and communication, along with restricted and repetitive behaviors. Both genetic and environmental factors contribute to ASD, with prenatal exposure to valproic acid (VPA) and nicotine being linked to increased risk. Impaired adult hippocampal neurogenesis, particularly in the ventral region, is thought to play a role in the social deficits observed in ASD.MethodsIn this study, we investigated social behavior and adult hippocampal neurogenesis in C57BL/6J mice prenatally exposed to VPA or nicotine, as well as in genetically modified ASD models, including IQSEC2 knockout (KO) and NLGN3-R451C knock-in (KI) mice. Sociability and social novelty preference were evaluated using a three-chamber social interaction test. Adult hippocampal neurogenesis was assessed by BrdU and DCX immunofluorescence to identify newborn and immature neurons.ResultsVPA-exposed mice displayed significant deficits in social interaction, while nicotine-exposed mice exhibited mild impairment in social novelty preference. Both IQSEC2 KO and NLGN3-R451C KI mice demonstrated reduced adult neurogenesis, particularly in the ventral hippocampus, a region associated with social behavior and emotion. Across all ASD mouse models, a significant reduction in BrdU+/NeuN+ cells in the ventral hippocampus was observed, while dorsal hippocampal neurogenesis remained relatively unaffected. Similar reductions in DCX-positive cells were identified in VPA, nicotine, and NLGN3-R451C KI mice, indicating impaired proliferation or differentiation of neuronal progenitors.DiscussionThese findings suggest that impaired adult neurogenesis in the ventral hippocampus is a common hallmark across ASD mouse models and may underlie social behavior deficits. This study provides insight into region-specific neurogenic alterations linked to ASD pathophysiology and highlights potential targets for therapeutic interventions.